Ammonite biostratigraphy and bioevents in the Jurassic - Cretaceous boundary of central Chile - Salazar Soto, Christian; Stinnesbeck, Wolfgang; Alvarez, Miguel (Cretaceous research, 2020)
Ammonites are abundant and well preserved in the Tithonian-Valanginian (Upper Jurassic - Lower Cretaceous) sedimentary successions of the central Chilean Andes, known as the Lo Valdés and Baños del Flaco Formations. A total of 1429 ammonites were collected from these stratigraphic units and the following index zones based on ammonites are here proposed, from base to top: Virgatosphinctes mexicanus/Pseudolissoceras cf. zitteli, Windhauseniceras internispinosum, Micracanthoceras microcanthum/Corongoceras alternans, Substeueroceras koeneni (Berriasella fraudans and Groebericeras rocardi sub-zones) and Thurmanniceras thurmanni/Argentiniceras fasciculatum. Our analyses indicate that “Ammonite Richness” is high in the middle and upper Tithonian and into the lower Berriasian part of the succession, but decreases towards the lower Valanginian. Highest similarity values are established for the upper Tithonian, coincident with a high diversity; similarity declines in the lower Berriasian. The main faunal turnover occurred between the early and late Berriasian followed by a secondary bioevent between the late Berriasian and early Valanginian.
Available online 24 October 2019
Gesehen am 22.04.2020